第14次南極地域観測隊夏隊報告1972-1973 - 楠, 宏; クスノキ, コウ; KUSUNOKI, Kou (国立極地研究所, 1974)
P(論文) Summer relief operations of the 14th JARE led by the present author are reviewed, including a description of a new official procedure of appointment of the expedition personnel and expenditures. The icebreaker FUJI, carrying 40 expedition members and 500 tons of cargo and equipped with three helicopters, made a voyage to Syowa Station in Antarctica from 25 November 1972 to 20 April 1973. After calling at Fremantle in Western Australia, the ship reached the offing of Syowa Station on 1 January 1973, and the transportation of cargo by means of helicopters was continued until 12 February. Due to thick many-wintered fast ice, the ship failed to cut the channel to the Station, hence about 27 tons of heavy materials were not delivered. Scientific activities were largely the continuation from previous years; shipboard oceanographic observations, measurements of cosmic-rays intensities and radio wave intensities were carried out throughout the voyage. About a dozen of field research parties were dispatched to the exposed rock areas in the vicinity of Syowa Station, including an oversnow return trip to the Mizuho Camp in the inland. One successful launching of the S210-JA16 sounding rocket was carried out on 15 February. On 20 February the wintering party officially took over the duties, and the ship left the Antarctic on the 24th and returned to Tokyo via Cape Town and Singapore. departmental bulletin paper